Amorphophallus Minimus (Araceae), A New Species From the Montane Forest of Nueva Ecija, Luzon Island, Philippines - Bustamante, Rene Alfred Anton (Archīum Ateneo, 2021)
Amorphophallus minimus (Araceae) is herein described and illustrated as a new species from the montane forest of Nueva Ecija; Luzon island; Philippines. A. minimus has an overall resemblance to Amorphophallus palawanensis Bogner and Hett.; however; it is easily distinguished by having a club-shaped and colliculate appendix that is contiguous with the male zone; oblate stamens (2 per flower); presence of leaf bulbils; and its overall small dimensions. Amorphophallus minimus is currently the only species in the Philippines found to inhabit a montane forest ecosystem.